2020
DOI: 10.3390/ijerph17062047
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Cardiovascular Disease Risk by Socioeconomic Status (SES) of Workers Using National Health Information Database

Abstract: The socioeconomic status (SES) and health behaviors of workers are associated with the risks of developing obesity, diabetes, hypertension, hyperlipidemia, and other cardiovascular diseases. Herein, we investigated the factors influencing cardiovascular disease (CVD) risk based on the SES of male and female workers. This cross-sectional analysis used the National Health Information Database to assess the associations between gender, SES (income level, residential area), health behaviors, and CVD-related health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…20,21 Numerous studies have examined the association between socioeconomic status and the cardiovascular disease-related health status and they showed income and education levels are associated with obesity and abdominal obesity. 21,22 Our findings support that individuals with lower income and education levels have higher rates of obesity and abdominal obesity, including especially in females. Similar to our findings, a study using data from the NHIS database identified a sex difference in the prevalence and odds ratio of obesity and abdominal obesity in workers: those with a lower income or rural residence were correlated with obesity and abdominal obesity among female workers.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…20,21 Numerous studies have examined the association between socioeconomic status and the cardiovascular disease-related health status and they showed income and education levels are associated with obesity and abdominal obesity. 21,22 Our findings support that individuals with lower income and education levels have higher rates of obesity and abdominal obesity, including especially in females. Similar to our findings, a study using data from the NHIS database identified a sex difference in the prevalence and odds ratio of obesity and abdominal obesity in workers: those with a lower income or rural residence were correlated with obesity and abdominal obesity among female workers.…”
Section: Discussionsupporting
confidence: 72%
“…Similar to our findings, a study using data from the NHIS database identified a sex difference in the prevalence and odds ratio of obesity and abdominal obesity in workers: those with a lower income or rural residence were correlated with obesity and abdominal obesity among female workers. 22 This study explained that this difference can be attributed to variations in health behaviors between males and females. In addition, the disparity in obesity prevalence according to socioeconomic status observed in our study appeared to be more prominent when compared with findings from a previous study.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, people with poor SES are very prone to pseudo-science, to “off the record” non-medical advice and to the “fake-news” phenomenon concerning specific therapies, which can further prevent an early presentation to hospital and adequate treatment, thereby possibly inducing HF decompensation. This aspect is particularly evident during the COVID-19 pandemic period, when less developed countries, with a lower human development index or GDP/capita (mutually interchangeable with a low SES), present lower rates of vaccination and decreased adherence to sanitary preventive measures [ 38 ], a similar pattern also being observed in the case of reduced adherence to cardiometabolic medication or increased prevalence of various cardiovascular risk factors amongst individuals with modest SES [ 39 , 40 ]. Our results showed that residents of rural areas presented more severe systolic disfunction ( p = 0.009) and an increased need for positive inotropic support ( p = 0.0015) compared to urban dwellers; in this situation, delayed medical presentation or low treatment adherence are commonly incriminated risk factors [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that higher life-course socioeconomic status for both men and women was associated with increased odds of overweight/obesity, and additionally diabetes and hypertension for men in middle-income countries. Interestingly, that among the factors influencing cardiovascular disease (CVD) risk, both lower income and residence in rural areas were associated with higher CVD risk for male and female workers [14].…”
Section: Discussionmentioning
confidence: 99%